Feasibility Analysis of Investing in Additional Vehicles at An Egg Distributor - Yelita Anggiane Iskandar; Resista Vikaliana; Anggita Adiani Putri; Arif Irawan; Hanum Parinduri Nugroho; Nur Annisa Amalia; Tito Altis Irawan; Stenlee Rolandiaz (Universitas Mercu Buana, 2023)
Business or investment feasibility analysis is research into a business plan that will analyze whether the investment to be made is feasible or not. Amalia Bintang Telur is located in the Cibitung area, Bekasi, West Java and has a branch located in Kalibata, South Jakarta which is the object of this research. This distributor has vehicles in the form of Grandmax type pick-up cars. The car's carrying capacity is 1800 kg. The problem faced by this distributor is that there are frequent delays due to a lack of vehicles for distribution, while there is high demand to be met. Usually, in dealing with these delays, distributors negotiate first with customers. If not addressed, the level of customer satisfaction with this distributor will decrease. There are several methods used to analyze the feasibility of an investment, namely, NPV, PP, Interest Rate (IRR) and Sum off Years Depreciation. It is concluded that the investment in adding a pick up car is worth doing, seen from the resulting positive NPV value of Rp. 942,260,893.38, based on the payback method this investment period is worth doing because the return occurs in the 1st year which produces a cumulative value of positive, the IRR investment method is worth investing in because the IRR value obtained is greater than the MARR used, namely 399% > 15%. For depreciation value, car prices tend to decrease every year. In the first year, the book value decreases by 19.44%, but after that, the depreciation in value will slow down with the depreciation percentage continuing to decrease by 2.34% until the eighth year.